EBV‐positive diffuse large B‐cell lymphoma, not otherwise specified: 2018 update on diagnosis, risk‐stratification and management - Castillo, Jorge J. (2018)
Disease overview Epstein Barr virus‐positive (EBV+) diffuse large B‐cell lymphoma (DLBCL), not otherwise specified (NOS) is an entity included in the 2016 WHO classification of lymphoid neoplasms. EBV+ DLBCL, NOS, is an aggressive B‐cell lymphoma associated with chronic EBV infection, and a poor prognosis with standard chemotherapeutic approaches. Diagnosis The diagnosis is made through a careful pathological evaluation. Detection of EBV‐encoded RNA is considered standard for diagnosis; however, a clear cutoff for positivity has not been defined. The differential diagnosis includes plasmablastic lymphoma, DLBCL associated with chronic inflammation, primary effusion lymphoma, HHV8+ DLBCL, NOS, and EBV+ mucocutaneuos ulcer. Risk‐stratification The International prognostic index (IPI) and the Oyama score can be used for risk‐stratification. The Oyama score includes age >70 years and presence of B symptoms. The expression of CD30 is emerging as a potential adverse, and targetable, prognostic factor. Management Patients with EBV+ DLBCL, NOS, should be staged and managed following similar guidelines than patients with EBV‐negative DLBCL. EBV+ DLBCL, NOS, however, has a worse prognosis than EBV‐negative DLBCL in the era of chemoimmunotherapy. There is an opportunity to study and develop targeted therapy in the management of patients with EBV+ DLBCL, NOS.